Kajian Undang-Undang Desa 3 Tahun 2024: Narasi Perubahan - Abdillah, Ashar; Ham, Umirul; Fakruddin, Faiz (CV WAHANA PUBLIKASI, 2025)
This study aims to analyze how the Village Law has changed from Law Number 6 of 2014 to its amendment through Law Number 3 of 2024, as well as the objectives behind this alteration. The Village Law introduces a new dimension to village governance by positioning villages as strategic actors in regional development. This regulation provides broader space for the involvement of all stakeholders in village advancement and offers opportunities for villages to demonstrate their capacity and transform towards independence. Furthermore, the authority to establish and manage village institutions and to acquire sources of revenue enhances village autonomy in determining development directions. This research employs a qualitative approach. Data were collected through library research methods. In addition, data were obtained by reviewing relevant literature such as articles, books, and documents. The results indicate that the changes to the Village Law are expected to guide village governance towards prioritizing development, community building, and community empowerment based on Pancasila, the Constitution of the Republic of Indonesia, the Unitary State of the Republic of Indonesia, and Bhinneka Tunggal Ika in accordance with statutory regulations. The transformation of the policy from Village Law No. 6 of 2014 to Law No. 3 of 2024 is not merely an administrative adjustment, but rather an effort to reorient the paradigm of village development. This change illustrates that villages are no longer viewed as development objects dependent on the central government, but as political entities with greater authority, capacity, and flexibility in determining their own development pathways.